STIFFENER-SKIN INTERFACE FAILURE CHARACTERIZATION OF THE STIFFENED COMPOSITE PANEL AT POST-BUCKLING STAGE - HU BoTao; CHAI YaNan; CHEN XiangMing; WEI JingChao (Jixie qiangdu)
A six-point bending test that characterized the failure of the stiffener-skin interface of a stiffened composite panel at the post-buckling stage is studied. A FEM model for a stiffened panel subjected to compression and a six-point bending test model were created in Abaqus. The initial failure location,the failure model,and the stress distribution of the stiffener-skin interface of the six-point bending test were analyzed compared with a stiffened panel by using the cohesive element and the submodel method. Based on the results of the FEM model,running loads transferred through the bond layer were derived,failure criteria and failure envelops were developed for the stiffener/skin interface. The results indicate that the six-point bending test can characterize the interface failure of a composite stiffened panel at the post-buckling stage availably.